Preliminary results of productivity of Gochu Asturcelta’s breed in semi-extensive systems - De la Roza-Delgado B.; Cueto M.A.; Menéndez J.; Argamentería A. (7th International Symposium on the Mediterranean Pig, 2012)
The aim of this work was to carry out preliminary studies of productivity of Gochu Asturcelta´s breed in semiextensive systems. There were confirmed two different strategies of growing and fatteninig of an autochthonous endangered pig breed, following the recommendations given for Iberian pig. A total of 19 animals in 2008 and 22 in 2009 were tested. The first strategy used rearing feed ad libitum from the weaning, except a restriction to 2.5 kg pig-1day-1 in the last month. In other one, the rearing feed was replaced to five months postwean for other feed: growing ad libitum (from 5 to 8 months) and fattening to dose of 2-2.5 kg pig-1day-1. The finishing in both years was done with different proportions of non-transgenic cereals. There were no differences in the live weight curves of evolution in both cases, turning out to be a better feed conversion rate with the second strategy (5.1 vs 5.3). The results showed that it is interesting to shorten the initial period of supply ad libitum and to restrict later to 2-2.5 kg pig-1day-1, using feed mixtures with 3200 kcal of digestible energy/kg dry matter and 10-12% crude protein, similar to those of the Iberian pork. However, further work is needed to investigate the effects of feeding levels on growth and meat quality of Gochu Asturcelta pig.
7. International Symposium on the Mediterranean Pig, 2010/10/14-16, Córdoba (Spain)